2007
DOI: 10.1111/j.1600-6143.2006.01721.x
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Anti-HLA-Specific Antibody Strength in Monitoring Kidney Transplant Patients

Abstract: Approximately 25% of patients who undergo kidney transplantation develop HLA-specific antibodies, the strength of which has not been previously correlated with graft failure. The strength of these de novo antibodies is investigated in this study. Serial dilution of strong HLA-specific allo-antibodies (up to 1:25,600) and testing with HLA-antigen-coated beads showed that the titer of the reaction to different HLA antigens is directly correlated to maximum fluorescence values and the molecules of equivalent solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
78
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(84 citation statements)
references
References 8 publications
4
78
1
1
Order By: Relevance
“…Not only the specificity but also the strength of the antibody can be determined in a Luminex test by MFI or molecules of equivalent soluble fluorochrome (MESF) values (Figure 1). The titers of the anti-HLA antibodies were correlated with MESF values (56). An increasing number of recent studies demonstrated an association between the strength of DSAs and risk of development of AMR, response to treatment of AMR, allograft survival, and success of desensitization protocols.…”
Section: Current Problems In Desensitization Protocolsmentioning
confidence: 96%
“…Not only the specificity but also the strength of the antibody can be determined in a Luminex test by MFI or molecules of equivalent soluble fluorochrome (MESF) values (Figure 1). The titers of the anti-HLA antibodies were correlated with MESF values (56). An increasing number of recent studies demonstrated an association between the strength of DSAs and risk of development of AMR, response to treatment of AMR, allograft survival, and success of desensitization protocols.…”
Section: Current Problems In Desensitization Protocolsmentioning
confidence: 96%
“…These antibodies can be detected with the complement‐dependent cytotoxicity crossmatch assay (CDC‐XM), which has been the gold standard since 1969. With the more recently developed single antigen bead (SAB) assays, DSAs can be detected with increased sensitivity and specificity,9 but the relation between these SAB assay–detected antibodies and clinical outcome is still unclear 10, 11, 12, 13, 14. The presence of SAB assay–detected antibodies that do not cause a positive CDC‐XM is not a contraindication for transplant but may indicate an increased immunological risk for rejection and allograft loss 15…”
Section: Introductionmentioning
confidence: 99%
“…3 Studies of the clinical relevance of HLA-DSA in patients who receive a transplant with a negative CXM have been contradictory. 6 -9 The ability to quantify these antibodies 10 has added a dimension of complexity to the equation. The semiquantitative ELISA technique was used to advantage by our group in a cohort of 237 patients with renal transplants, showing an increase in the occurrence of acute antibody-mediated rejection (AMR) with increasing HLA-DSA levels detected in historic sera.…”
mentioning
confidence: 99%